2010
DOI: 10.1007/s10664-010-9143-7
|View full text |Cite
|
Sign up to set email alerts
|

Studying the co-evolution of production and test code in open source and industrial developer test processes through repository mining

Abstract: Many software production processes advocate rigorous development testing alongside functional code writing, which implies that both test code and production code should co-evolve. To gain insight in the nature of this co-evolution, this paper proposes three views (realized by a tool called TeMo) that combine information from a software project's versioning system, the size of the various artifacts and the test coverage reports. We validate these views against two open source and one industrial software project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 54 publications
(49 reference statements)
5
110
0
3
Order By: Relevance
“…As it can be seen, while the Code line smoothly increases over time, the Test line frequently stays constant across revisions, indicating that testing is often a phased activity [41], that takes place only at certain times during development. One exception is Git, where code and tests evolve more synchronously, with a large number of revisions modifying both code and tests.…”
Section: Code and Test Evolutionmentioning
confidence: 96%
See 2 more Smart Citations
“…As it can be seen, while the Code line smoothly increases over time, the Test line frequently stays constant across revisions, indicating that testing is often a phased activity [41], that takes place only at certain times during development. One exception is Git, where code and tests evolve more synchronously, with a large number of revisions modifying both code and tests.…”
Section: Code and Test Evolutionmentioning
confidence: 96%
“…Zaidman et al [41] have examined the co-evolution of code and tests on two open-source and one industrial Java applications. The study looks at the evolution of program coverage over time, but only computes coverage for the major and minor releases of each system, providing around ten data points for each system.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the quality of test cases is important to ease their maintenance [1,23], it was shown that test smells, i.e., symptoms of possible design issues of the test code [22], are very spread both in open source and industrial code; moreover, they have a strong impact on comprehension and maintenance [3]. This situation is even worse in automatically generated test cases, since they are more affected by test smells than their manually written counterparts [16].…”
Section: Introductionmentioning
confidence: 99%
“…While automated test suites are helpful from a (continuous) integration and regression testing perspective, they lead to a substantial amount of test code [16]. Like production code, test code needs to be maintained, understood, and adjusted upon changes to production code or requirements [8,10,13].…”
Section: Introductionmentioning
confidence: 99%